Estado fiscal e as suas disfunções, impactos da economia digital e o dever solidário de custeio dos direitos fundamentais no Brasil - Sipolatti, Gustavo (2024)
Thesis carried out in the Doctorate in Fundamental Rights and Guarantees of the Faculty of Law of Vitória (FDV), in the nucleus of the Research Group State and Constitution of Professor José Luis Bolzan de Morais, which proposed to answer the question: “How the Fiscal State should overcome its dysfunctions and also tax the digital economy?”. The theoretical basis adopted the concept of fundamental duty to pay taxes from Casalta Nabais. Through bibliographical research and the dialectical method, the theme was developed from modern contractualism, through Analog Economy and Technoliberalism, to arrive at a disruptive, fluid, innovative and borderless Digital Economy, in which the main wealth matrix, the capital, has been losing space for data and which, at the same time as it produces wealth, concentrates power, forms technological feuds, generates deleterious effects for society and impacts fundamental rights and duties. The ability of the tax system to deal with this problem was then analyzed: its traditional paradigms, the principles of legality and legal certainty, the appreciation of dogmatics for the norm and its formal validity, the hierarchy of qualified structures, the self-referential schemes and the extensive list of taxpayers' rights. The approach also turned to concrete cases. The focus was on the dysfunctions of the Powers (Executive, Legislative and Judiciary), on the excess of formalism, on the normative and bureaucratic complexity, on their social incomprehension, on the direction of collection and benefits by interest groups, on the privilege of oligopolies, on the regressivity, in the protagonism of the federal executive, in the absence of regulation and in the deficit of democratic participation in the organs of power. Therefore, the analogical State proved to be dysfunctional and also not prepared to tax the digital economy, with a breach of the fundamental duty to pay taxes, especially for technological feuds, leading to fiscal apartheid. In the end, as a response, at the international level, the creation of a new system is proposed, with a gravitational core in the understanding of the common, solidary and universal responsibility to fund the State through taxes, in order to maintain the social fabric and fight poverty, through a tax law negotiated and subsidiarily signed between nations and with the participation of these large technology companies, with the creation of a global tax on digital operations, covering the different matrices of wealth, data and capital . At the national level, preserving the autonomy of the States and being aware of the limits of territoriality, democratic participation in the centers of power must be ensured and 9 encouraged, with the creation and application of law in line with the creation of conditions for the realization of elected interests, with the republican metric for constant revision of its impacts, dethroning the paradigms of formal legality, the crystallization of injustices by the mantle of legal security and the culture of conceptualism, which have served to protect local and foreign oligopolies, increasing poverty and inequalities, all with the declared bias of rescuing the original and civilizing purposes that justified the creation of the State